La precarización laboral en las floricultoras de la ciudad de Tabacundo año 2021. - Chorlango Cuzco, Alexis Rene (2023)
Law is a source of social and legal development where the protection of the human being through universal rights has prevailed for the national benefit; The constant need for labor in the Ecuadorian territory has emanated norms that regulate the dependency between employer and worker, therefore, the Ecuadorian state through the magna carta recognizes work with a terminology of a "social" nature with the purpose of solving and providing the due both administrative and regulatory protection of the worker in the workplace. The labor necessity in the urban and rural context have marked differences in the salary remuneration by the employer towards the worker; labor law has been restricted and violated by inefficient working conditions imposed on the floricultures. The principles of labor law and the formal sources of law indicate essential rights, guarantees and duties to be established in the state of rights and social justice, therefore, job insecurity in Ecuador is an essential point to address for the benefit and application of the law. pro operator principle and in the same way, make effective the Pro homine principle. The economic boom for the export of roses and their varieties has currently positioned the productive sector of the Pedro Moncayo Canton as a source of jobs for men and women; jointly the floricultures have influenced the creation of inefficient standards in the contractual relationship, generating the violation of labor rights established in the Constitution of the Republic of Ecuador and the Labor Code. It should be noted, the lack of regulation and control towards small, medium and large flower growers that are offering their commercial activities in the Pedro Moncayo Canton; Young people, women, men and older adults, by providing their "labor" services in these spaces, are forced into precarious conditions that violate aspects such as: health, labor dignity, decent wage, social security. Even the "Covid-19" health emergency generated a setback in the labor law of Ecuador due to the ineffective application of the law and legal protection of the state towards constitutional rights, principles and guarantees. But, these harmful aspects of the law need to be investigated and treated in order to offer necessary actions for the social and collective well-being of workers; Aspects such as rights, attributions and obligations of workers and employers must be analyzed to present better public actions that specify the applicability of labor, constitutional and international regulations. In turn, establish the doctrine and jurisprudence that responds 4 to the social need to prioritize control over the employer's obligations in the different work spaces offered by small, medium and large flower growers in the city of Tabacundo. The present investigation, through the correct methodological application assents, promotes a legal and doctrinal analysis of labor precariousness in the contractual scope of the employer and worker, and through the bibliographic and descriptive method it is visualized, the work environment, the work space in flower growers ; together with the fulfillment of the rights and obligations of the employer with the worker and vice versa. Key words: Precariousness, Labor Law, Work Environment, Dignified Employment, Flowers.